Courageously critiquing sexual violence: responding to the 2018 Nobel Peace Prize. (1st November 2019) - Stern, Maria
Abstract: Marysia Zalewski's work has taught us, as a collective of feminist scholars, to be cautious of neat instruction manuals and coherently set out plans of action; of claims to sure knowledge about danger, violence, and its subjects and remedies; of the fanfare of grand arrivals; and of the quieter staking of ground that has been seemingly won. Zalewski has persistently reminded us in different ways that we/she does 'not even know what gender is or does'. Far from a flippant response to the emptiness of gender mainstreaming policies, this seemingly simple statement instead serves as a glaring post-it note on the margins of our texts about International Relations theory, feminism, sex/gender and violence— both those that we read, as well as those that we write. However, this lesson is often forgotten in our rush to understand and establish gendered harms as valid and important, and to seek their redress. Gleaning insights from Zalewski's work, this article critically considers possible responses to the 2018 Nobel Peace Prize. Its aim is not to delve into a discussion of the politics or effects of the Peace Prize as such, but to instead use the 2018 Peace Prize as a marker—a moment to consider the possibility for critique in relation to sexual violence.